The End of Iceland's Innocence. The Image of Iceland in the Foreign Media during the Crisis - Chartier, Daniel (Citizen Press, 2010)
In the space of a few days, in 2008, one of the world’s richest and most egalitarian nations, Iceland, toppled into financial chaos and sunk into an economic, ethical, moral and identity crisis. The vast empire built by Iceland’s young entrepreneurs, the 'new Vikings’-who had propelled the country to the top of wealth, equality and happiness charts-collapsed under the combined effect of the failure of its banks and astronomical debt {more than ten times the country's gross domestic product). Iceland became, in the midst of the global economic crisis, an icon of disaster that concerns all Western countries seeking to understand how the Scandinavian model could collapse so suddenly. In this book, Daniel Chartier traces, through thousands of articles appearing in the foreign press, the fascinating reversal of Iceland’s image during the crisis. Iceland now faces significant issues, involving its image in the world, the rebuilding of trust and even the future of its sovereignty.